Estilos de vida y su relación con el rendimiento escolar en los estudiantes del Colegio Técnico Agropecuario 29 de Mayo de la Parroquia de Guachanamá, cantón Paltas, provincia de Loja - Torres Jaramillo, María Isabel (2015)
This research work is a study of quantitative and prospective cross-cutting issues; it has the purpose of determining students’ performances, including their lifestyles and their school community relationship, of the Agricultural Technical "May 29” high school, which is located in Guachanamá town in Canton Paltas, Loja Province. The sample consists of 80 who were administered the questionnaire lifestyle profile , instrument having reliability coefficient Cronbach's alpha of ,8317 the questionnaire (FIFO-II) consists of 54 items, allowing qualify for healthy lifestyles : good, fair and bad, which make up 8 scales, including nutrition, exercise, health responsibility, stress management, interpersonal support, dreams, and substance abuse. Using Microsoft Excel 2013 for statistical data, the results indicate that for our study group, 83% maintain an optimal school performance, and 14% have an inadequate school performance. Therefore, we can sum up that studied lifestyles correlate with 16%, equivalent to 13 students who have a low lifestyle. This work gradually shows that the students have a meaningful relationship between their lifestyle and academic performance in high school. Key words: Lifestyle, school performance.